2020
DOI: 10.1186/s12864-020-6705-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of Sphaerospora molnari (Cnidaria, Myxosporea) blood stages provides proteolytic arsenal as potential therapeutic targets against sphaerosporosis in common carp

Abstract: Background: Parasites employ proteases to evade host immune systems, feed and replicate and are often the target of anti-parasite strategies to disrupt these interactions. Myxozoans are obligate cnidarian parasites, alternating between invertebrate and fish hosts. Their genes are highly divergent from other metazoans, and available genomic and transcriptomic datasets are limited. Some myxozoans are important aquaculture pathogens such as Sphaerospora molnari replicating in the blood of farmed carp before reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 90 publications
3
22
0
Order By: Relevance
“…2005 ), and this appears similar in myxozoans: ∼2.5% (422 proteins) in the Thelohanellus kitauei proteome ( Yang et al. 2014 ) and 2.6% of expressed genes in Sphaerospora molnari ( Hartigan et al 2020 ). Our relative frequency analyses showed that these genes are generally less conserved/more variable in C. shasta than cell migration genes.…”
Section: Discussionmentioning
confidence: 72%
“…2005 ), and this appears similar in myxozoans: ∼2.5% (422 proteins) in the Thelohanellus kitauei proteome ( Yang et al. 2014 ) and 2.6% of expressed genes in Sphaerospora molnari ( Hartigan et al 2020 ). Our relative frequency analyses showed that these genes are generally less conserved/more variable in C. shasta than cell migration genes.…”
Section: Discussionmentioning
confidence: 72%
“…PRJNA241036) [ 32 ]; Sphaerospora molnari (BioProject No. PRJNA522909) [ 33 ]; Thelohanellus kitauei (BioProject No. PRJNA193083) [ 27 ]; Enteromyxum leei (BioProject No.…”
Section: Methodsmentioning
confidence: 99%
“…The upregulation of protease inhibitors may reflect a finely adapted innate immune defense system in bryozoans that is capable of monitoring self- and parasite-derived proteases and that may inactivate and eliminate the proteases involved in parasite invasion [ 29 , 30 ]. Proteases of myxozoans have been described as major virulence factors and are assumed to support the invasion of parasites into their hosts [ 31 , 32 , 33 , 34 ]. Similarly, proteases have been identified in T. bryosalmonae using RNA-seq analysis (authors own unpublished data).…”
Section: Discussionmentioning
confidence: 99%